Efektivitas Alur Pengelolaan Sarana dan Prasarana Pendidikan terhadap Mutu Pembelajaran - Mutia Adilah Zahra; Janah, Lutfiatul; Syihab, Naufal; Munawwaroh, Zahrotul (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The success of education delivery depends heavily on the quality of supporting elements, particularly educational facilities, which play a strategic role in supporting learning activities and achieving human resource development goals. This research is motivated by a gap in understanding regarding the effectiveness of the management process for facilities and infrastructure in improving learning quality, as well as the need to adapt to the dynamics of modern education. The purpose of this research is to examine the management process for educational facilities and infrastructure and its contribution to improving learning quality, based on the results of a literature review. The method used in this research is a descriptive qualitative approach with a literature review method, where data was obtained through critical analysis of scientific journals and academic literature. The research findings indicate that the management of educational facilities and infrastructure includes the stages of planning, procurement, inventory, utilization, maintenance, supervision, and disposal. Each stage is interrelated and plays a strategic role in supporting a more effective, efficient, and sustainable learning process. The implications of this research indicate that the management of educational facilities and infrastructure, carried out through a planned and sustainable process, plays a crucial role in supporting the improvement of learning quality.